Desentralisasi Fiskal dan Ketimpangan Pendapatan - Steffi Kartika Satriya (Lembaga Pengembangan Kinerja Dosen, 2026)
Income inequality remains a fundamental challenge in regional economic development after the implementation of regional autonomy. This study aims to analyze the effect of fiscal decentralization policies, as measured by the variables of Local Government Revenue (LGR) and the Balancing Fund, on income inequality in 14 regencies/cities in West Kalimantan Province. This study uses a descriptive quantitative approach with panel data for the period 2015–2024. The data analysis technique used is panel data regression with a natural logarithm model. The results of the study show that LGR has a positive and significant influence on income inequality, which indicates that increasing regional fiscal independence actually tends to widen income disparity. Conversely, the Balancing Fund is proven to have a negative and significant effect, confirming its effective role as a redistribution instrument in reducing interregional inequality. Simultaneously, both fiscal instruments have a significant impact on the Gini ratio.